2000
DOI: 10.1590/s0074-02762000000300004
|View full text |Cite
|
Sign up to set email alerts
|

Oswaldotrema nacinovici gen. nov. sp. nov. (Digenea: Philophthalmidae) from Numenius phaeopus (Aves: Scolopacidae) in Brazil

Abstract: shape, head, esophagus, pharynx, acetabulum, vitellaria, vitelline reservoir and seminal vesicle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Trematodes of whimbrels had already been subjects of studies. The specimens diagnosed as O. nacinovici in this study was the same as that reported previously in Brazil [ 22 ]. This relatively new genus ( Oswaldotrema ) is similar or related to genera Pittacium, Cloacitrema, Parorchis , and Pygorchis .…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Trematodes of whimbrels had already been subjects of studies. The specimens diagnosed as O. nacinovici in this study was the same as that reported previously in Brazil [ 22 ]. This relatively new genus ( Oswaldotrema ) is similar or related to genera Pittacium, Cloacitrema, Parorchis , and Pygorchis .…”
supporting
confidence: 69%
“…The present report is to refer Oswaldotrema nacinovici , a new parasite fauna which parasitizes N. phaeopus birds in Korea. This new trematode was originally reported from N. phaeopus in Brazil [ 22 ]. However, detailed information on parasites of N. phaeopus is still lacking in Brazil because of its migratory habits.…”
mentioning
confidence: 99%